Dual training and adult education in agricultural vocational training: Az agrárszakképzés és a hozzá kapcsolódó felnőttképzés és duális képzés kialakulása Magyarországon - Városi, Klára (Acta Carolus Robertus, 2023)
The legal and legislative background dealing with vocational training and adult education has undergone several changes over the past almost sixty years. In addition to social policy and national economic effects, the changes were also strongly influenced by the vocational training policies of the countries around us. Through these changes, I would like to show how today’s dual education system developed in agricultural vocational training, and what place adult education have been given in this model. It can be seen in the Hungarian VET culture that cooperation with dual internships is managed by the VET based on legal compliance and is mainly based on the documentation system. The international outlook shows a market-based cooperation model.